Positivity Effect and Working Memory Performance Remains Intact in Older Adults After Sleep Deprivation - Gerhardsson, Andreas; Fischer, Håkan; Lekander, Mats; Kecklund, Göran; Axelsson, John; Åkerstedt, Torbjörn; Schwarz, Johanna (Frontiers in Psychology, 2019)
Background: Older adults perform better in tasks which include positive stimuli, referred to as the positivity effect. However, recent research suggests that the positivity effect could be attenuated when additional challenges such as stress or cognitive demands are introduced. Moreover, it is well established that older adults are relatively resilient to many of the adverse effects of sleep deprivation. Our aim was to investigate if the positivity effect in older adults is affected by one night of total sleep deprivation using an emotional working memory task. Methods: A healthy sample of 48 older adults (60-72 years) was either sleep deprived for one night (n = 24) or had a normal night’s sleep (n = 24). They performed an emotional working memory n-back (n = 1 & 3) task containing positive, negative and neutral pictures. Results: Performance in terms of accuracy and reaction times was best for positive stimuli and worst for negative stimuli. This positivity effect was not altered by sleep deprivation. Results also showed that, despite significantly increased sleepiness, there was no effect of sleep deprivation on working memory performance. A working memory load × valence interaction on the reaction times revealed that the beneficial effect of positive stimuli was only present in the 1-back condition. Conclusion: While the positivity effect and general working memory abilities in older adults are intact after one night of sleep deprivation, increased cognitive demand attenuates the positivity effect on working memory speed.